An Epidemiological Analysis of COVID-19 cases from Jan to July 2020 in Kelantan, Malaysia - Hazlienor Mohd Hatta; Nik Mohd Hafiz Mohd Fuzi; Nur Dalilah Mohd Zin; Afiq Izzudin A Rahim; Najihah Mahfuzah Zakria; Suhaiza Sulaiman; Abdul Haris Muhammad; Zaini Hussin (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 01-2021) [April 2021]